Bioethanol Production from Sugarcane Bagasse by a Novel Brazilian Pentose Fermenting Yeast Scheffersomyces shehatae UFMG-HM 52.2: Evaluation of Fermentation Medium - F. A. F. Antunes; A. K. Chandel; T. S. S. Milessi; J. C. Santos; C. A. Rosa; S. S. da Silva (International Journal of Chemical Engineering)
Bioconversion of hemicellulosic sugars into second generation (2G) ethanol plays a pivotal role in the overall success of biorefineries. In this study, ethanol production performance of a novel xylose-fermenting yeast, Scheffersomyces shehatae UFMG-HM 52.2, was evaluated under batch fermentation conditions using sugarcane bagasse (SB) hemicellulosic hydrolysate as carbon source. Dilute acid hydrolysis of SB was performed to obtain sugarcane bagasse hemicellulosic hydrolysate (SBHH). It was concentrated, detoxified, and supplemented with nutrients in different formulations to prepare the fermentation medium to the yeast evaluation performance. S. shehatae UFMG-HM 52.2 (isolated from Brazilian Atlantic rain forest ecosystem) was used in fermentations carried out in Erlenmeyer flasks maintained in a rotator shaker at 30°C and 200 rpm for 72 h. The use of a fermentation medium composed of SBHH supplemented with 5 g/L ammonium sulfate, 3 g/L yeast extract, and 3 g/L malt extract resulted in 0.38 g/g of ethanol yield and 0.19 g L.h of volumetric productivity after 48 h of incubation time.